Esthetic and Healing Outcomes of Oral Fibroma Excision Using a Diode Laser: A Case Report - Ahmed Ali Shnawa; Hanan J. Taher; Afrah A.Khalil (Iraqi Journal of Laser, 2025)
This case report evaluates the clinical outcomes of oral fibroma excision using a 980 nm diode laser, focusing on its effectiveness in reducing postoperative discomfort, promoting healing, and improving esthetic outcomes. A 980 nm diode laser was used in CW mode at 2 watts of power to remove two fibrous masses on the buccal mucosa from a 65-year-old male patient who had presented with these lesions. The procedure was performed under local anesthesia using 2% lidocaine with 1:80,000 epinephrine. Postoperative evaluations were performed at follow-up visits on the 3rd day, 1st week, 2nd week, and 4th week to evaluate bleeding, pain, edema, functional interference, mucosal scarring, and healing through standardized clinical indices. At each follow-up visit, photographic documentation was collected to objectively track the healing progress. The procedure resulted in no bleeding, no postoperative swelling, and mild pain that did not necessitate analgesics. The recovery of function was swift. Esthetic evaluation revealed no scarring on the left side and a minor scar on the right side, with excellent overall appearance. The left fibroma site underwent complete healing by the second week, whereas the right site necessitated four weeks for full reepithelialization. The results showed that the 980 nm diode laser is a suitable substitute for traditional scalpels for oral soft tissue surgery, with few complications, mild pain after the procedure, and fast healing time. This case highlights the clinical advantages of diode lasers in minor oral surgical procedures and supports their broader adoption in clinical practice.